1993
DOI: 10.1073/pnas.90.8.3251
|View full text |Cite
|
Sign up to set email alerts
|

Precursor polyprotein for multiple neuropeptides secreted from the suboesophageal ganglion of the silkworm Bombyx mori: characterization of the cDNA encoding the diapause hormone precursor and identification of additional peptides.

Abstract: Peptidergic neurons, which serve as source of various endocrine neuropeptides, were identified in the suboesophageal ganglion (SG) and brain of insects. In the silkworm Bombyx mori, SG is known to secrete two neuropeptides, diapause hormone (DH) responsible for induction ofembryonic diapause and pheromone biosynthesis-activating neuropeptide, which share a pentapeptide amide, Phe-Xaa-Pro-Arg-Leu-NH2 (Xaa = Gly or Ser), at the C terminus. We have isolated cDNA clones for DH from the cDNA library of SG by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(116 citation statements)
references
References 27 publications
2
114
0
Order By: Relevance
“…In some butterfly and moth species, synthesis and release of pheromones are regulated by pheromone biosynthesis activating neuropeptides (PBANs). The first PBANs identified from brain and subesophageal ganglia contain 33 or 34 amino acids, amidated at the C-terminus [5,14,16,24,27]. Despite significant advances over the last decades [4,10], many questions regarding the precise functional roles of PBANs remain.…”
Section: Introductionmentioning
confidence: 99%
“…In some butterfly and moth species, synthesis and release of pheromones are regulated by pheromone biosynthesis activating neuropeptides (PBANs). The first PBANs identified from brain and subesophageal ganglia contain 33 or 34 amino acids, amidated at the C-terminus [5,14,16,24,27]. Despite significant advances over the last decades [4,10], many questions regarding the precise functional roles of PBANs remain.…”
Section: Introductionmentioning
confidence: 99%
“…In B. mori, the DH precursor peptide can give rise to DH and other four additional FXPRL neuropeptides, the pheromone biosynthesis activating neuropeptide (PBAN) and the suboesophageal ganglion neuropeptides (a-, b-, c-SGNPs) [91,92]. DH, synthesized at the level of SOG of the silkworm, is released via the CC/CA complex in the haemolymph and it signals directly to egg chambers during vitellogenesis to elicit embryonic diapause (Fig.…”
Section: Embryonic Diapause and Diapause Hormone Signallingmentioning
confidence: 99%
“…The maternal SOG regulates embryonic state by producing diapause hormone (DH), which is a 24-amino acid peptide with a FXPRL motif at the C-terminus (X = G, T, V, S, I). The silkworm DH is encoded by the DH-PBAN gene that is expressed in neurosecretory cells (DHPCs) of the SOG, under the positive control of B. mori Pitx, a bicoid-like homeobox transcription factor that binds a cis-regulatory element in the promoter region of DH-PBAN [90][91][92]. Mammalian Pitx1 encodes an activator of pituitary-specific promoters such as those of genes encoding growth hormone (GH), prolactin (PRL), pro-opiomelanocortin (POMC), luteinizing hormone b-subunit (LHb), follicle stimulating hormone (FSH), and thyroid stimulating hormone (TSH) [93].…”
Section: Embryonic Diapause and Diapause Hormone Signallingmentioning
confidence: 99%
“…5) Recently, we cloned the cDNA for the Bomhyx PBAN, designated Type-A, from adult female moths (heterozygous Bombyx strain 11 06 x Daizo) usually used for the bioassay. b) The nucleotide sequence showed that the gene encodes, in addition to PBAN, diapause hormone, and three other putative amidated peptides structurally related to PBAN, and the sequence of the coding region is completely matched with that obtained by Sato et al 7) During the previous study, we found a partial cDNA the nucleotide sequence of which differs from Type-A cDNA's.…”
mentioning
confidence: 85%